Fossil woods with evidence of wood-decay by fungi from the Upper Cretaceous (Bajo Barreal Formation) of central Argentinean Patagonia. (August 2022) - Greppi, Carlos D.; Alvarez, Bruno; Pujana, Roberto R.; Ibiricu, Lucio M.; Casal, Gabriel A.
Abstract: An assemblage of seven silicified fossil woods from the Upper Cretaceous Bajo Barreral Formation, Chubut Province, Argentina is described. The anatomy of the woods indicates that they are related to the Araucariaceae and the Cheirolepidiaceae families. The specimens are placed into two taxonomic units: Agathoxylon antarcticus and Brachyoxylon patagonicum . The presence of both families suggests that they were canopy dominants as well as the main components of the forests during the early Late Cretaceous of central Patagonia. The growth rings indicate seasonality and that the woods came from mature trees. Two Brachyoxylon woods show decay patterns comparable to white rot caused by modern fungi. In addition, the presence of traumatic resin canals in the woods, the development of resins and cell wall apposition in the cell lumens suggest defensive responses on the part of the host plants. Highlights: We studied fossil woods from the early Late Cretaceous of Argentinean Patagonia. All the specimens are conifer woods. Two fossil species were found, Agathoxylon antarcticus and Brachyoxylon patagonicum. Two Brachyoxylon woods show rotting patterns by xylophagous fungi. Defensive barriers in Brachyoxylon woods suggest responses against pathogenicity.